Piercing [videorecording (DVD)] - Pesce, Nicolas, 1990-; Abbott, Christopher, 1986-; Wasikowska, Mia, 1989-; Costa, Laia, 1985-; Murakami, Ryū, 1952- (Universal Pictures Home Entertainment, 2019)
Reed leaves his wife and infant son to go on a business trip when he's actually planning a meticulous murder. He checks into a hotel and calls a prostitute as his unsuspecting victim. But Jackie is more than he bargained for, and after an unexpected disruption, the balance of power sways. Who's playing whom? As the night wears on, it becomes a nightmare of blood that will bond the two forever.